Analysis of the influence of the geometric features of the filler on the thermal properties and structure of the composites in the polypropylene matrix - Postawa, Przemysław; Jeż, Bartłomiej; Sylwester Norwiński; Kalwik, Aleksandra (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
The article presents the results of research on polymer composites based on polypropylene filled with various fillers. The physical and thermal properties of the composites are the result of the used polymer matrix as well as the properties and geometric features of the used filler. The geometric shape of the filler is particularly important in the processing of plastics in which the flow is forced, and high shearing tension occurs, which determines the high macromolecular orientation and specific arrangement of the filler particles. Thermal analysis (STA) was used in the research and photographs were taken using a scanning electron microscope (SEM) of fractures of polymer composites. The following fillers were used: talc, fibreglass, glass beads, and a halogen-free nitrogen-phosphorus flame retardant. The test material was obtained by extrusion. Shapes for strength tests, which were subjected to scanning microscopy tests after a static tensile test, were obtained by injection. The carried-out tests allowed us to determine the influence of the type and shape of individual fillers on structural changes in the structure of polypropylene composites and the degree of sample weight loss in a specific temperature range, depending on the used filler.